COVID-19, stability and regulation : evidence from Indonesian banks - PUTRA, PAMUNGKAS; Taufiq, Arifin; Irwan, Trinugroho; Evan, Lau; Bruno S., Sergi (Emerald Publishing Limited, 2023)
Purpose – This study aims to investigate the effect of credit relaxation policy during the COVID-19 pandemic and its efficacy as a countercyclical policy on bank risk and stability. Design/methodology/approach – Using a sample of 39 listed Indonesian banks, the authors investigate the effect of credit relaxation policy on banks’ risk and stability. Data were retrieved from Eikon DataStream from monthly financial statements from June 2019 to December 2020. The authors use panel data analysis with a fixed-effect estimator to estimate the model. Findings – The authors find that the credit relaxation policy affects banks’ stability. The authors also find no significant relationship between the policy and bank risk measured by non-performing loans. The authors also find that the policy mainly affects small banks and both state-owned and private banks. Originality/value – This research has some policy implications that issuing prompt regulations to respond to urgent situations is needed and is very important to face crisis conditions and reduce the negative impact of such crises.